Planning And Design Of Solar-Powered Electric Power System For Modern Kiosk - Febrianto, Fachrian Helga; Septian, Angga; Gunastuti, Dwi Anie; Solihin, Lili (Innovative: Journal Of Social Science Research, 2025)
Electric energy is important in human life, because almost all activities use electronic devices. Kiosks also have use of electrical energy. Small kiosks that can move around are not suitable for kWh meters (Grid). The solution is to utilize alternative energy in the form of Solar Power Plant, an independent energy producer by converting sunray into electric energy. Before system is built, planning is needed to get a reliable system. Method used to plan this system is R&D (Research & Development). The process includes: relevant studies, site(location) selection, load and energy consumption estimation, system design, component rating calculation, selection of components, design revisions, compiling budget plan, as well as conducting economic calculations. Planning results for a system with a load of 260 Watts and daily energy consumption of 1.1 kWh, system require 3 PV panels of 350 Wp, SCC rating 96V 60A max input with max power of 1440Watt at 24V, inverter 24/220V 50Hz with 1000Watt continuous and 2000Watt maximum power, battery bank with capacity of 300Ah 24V. System is feasible and profitable because it has a payback period (PP) value < PV panel lifetime, as well as an RoI (Return on Investment) percentage value of +11% profit.